Why are adolescent mothers more likely to have stunted and underweight children than adult mothers? A path analysis using data from 30,000 Bangladeshi mothers, 1996–2014 - Nguyen, Phuong; Scott, Samuel; Khuong, Long; Pramanik, Priyanjana; Ahmed, Akhter; Afsana, Kaosar; Menon, Purnima (Oxford Academic, 2022)
This article was published in Current Developments in Nutrition by Oxford Academic [ © Oxford University Press 2020.] and the definite version is available at: https://doi.org/10.1093/cdn/nzaa061_091 The Journal's website is at: https://academic.oup.com/cdn/article/4/Supplement_2/1463/5845785